2000
DOI: 10.1111/j.1469-8749.2000.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe bronchopulmonary dysplasia increases risk for later neurological and motor sequelae in preterm survivors

Abstract: Preterm children who develop severe chronic lung disease may be developmentally compromised by exposure to hypoxic episodes. This study aims to determine if children with severe bronchopulmonary dysplasia (BPD) who required home oxygen therapy were at greater risk for neurological and motor deficits at school age than preterm peers without BPD. This study evaluated 27 subjects with BPD and 27 preterm control infants matched for gestational age, birth weight, sex, and year of birth at a mean age of 9.9 years (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 47 publications
4
22
0
6
Order By: Relevance
“…This finding is consistent with Majnemer et al 28 who found that at 10 years of age, 50% of children with BPD who had required home oxygen therapy had gross and fine motor skill deficits. The findings are also consistent with outcomes found in this cohort at 3 years of age, which indicated that history of BPD predicted poor motor skills beyond the effects of other medical and demographic factors.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with Majnemer et al 28 who found that at 10 years of age, 50% of children with BPD who had required home oxygen therapy had gross and fine motor skill deficits. The findings are also consistent with outcomes found in this cohort at 3 years of age, which indicated that history of BPD predicted poor motor skills beyond the effects of other medical and demographic factors.…”
Section: Discussionsupporting
confidence: 92%
“…Children involved in the research project compared to the control group would seem to be characterized by social orientation, collaboration, and interaction abilities, which give them the chance to be extrovert and to activate exchanges and build relationships, which can also assure them the development of the abilities that they lack. These data are consistent with some studies of the field (Davis et al 2007;Gray et al 2008;Manjemer et al 2000;Winchester et al 2009;Ketharanathan et al 2011;Perricone & Morales 2011a, b;Perricone et al 2012a, b). These are abilities that can support the social success and scholastic contextualization of preterm children.…”
Section: Discussionsupporting
confidence: 91%
“…These risk factors include antenatal exposures, such as pregnancy-induced hypertension [6], gestational diabetes [7], and intrauterine inflammation [8][9][10], as well as male sex [11][12][13]. Putative perinatal and post-natal risk factors include early illness severity as measured by the Score of Neonatal Acute Physiology-Version II (SNAP-II) [14,15], infection [9,16,17], necrotizing enterocolitis [16,17], patent ductus arteriosus [18], chronic lung disease [18][19][20][21], and neonatal procedural pain [22]. We hypothesized that these ante-, peri-and postnatal comorbidities, rather than gestational age at birth, would predict poorer microstructural development in the corticospinal tract, as evidenced by higher mean diffusivity and lower fractional anisotropy in this motor pathway [23,24].…”
Section: Introductionmentioning
confidence: 99%